Efektivitas Pembayaran Kredit Melalui Aplikasi Pegadaian Digital Service Pada PT Pegadaian (Persero) Cabang Warung Jambu - Hamidah, Tiara Nur; Silaen, Uluan; Suharmiati, Suharmiati (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
Pegadaian Digital Service (PDS) is an application-based digital service that was officially launched by PT Pegadaian (Persero) on April 1, 2018. This application can be operated on customers' smartphones as an online means to find information and perform various transactions on products. existing at PT Pegadaian (Persero) and to expand the target market to the millennial generation. The purpose of the compiler in conducting this review is to find out how the credit payment procedure through the PDS application, what obstacles occur during the credit payment process through the PDS application, and how the effectiveness of credit payments through the PDS application at PT Pegadaian (Persero) Warung Jambu Branch. The results of a review conducted by the compiler at PT Pegadaian (Persero) Warung Jambu Branch showed that credit payments through the PDS application at PT Pegadaian (Persero) Warung Jambu Branch were still considered ineffective because there were still many customers who made credit payments directly through outlets compared to with the number of customers who make credit payments through the PDS application. As for the cause of this because many customers do not know information about the PDS application and understand the use of the PDS application as well as various disturbances in the application that make customers uncomfortable. Keywords: PT Pegadaian, Pegadaian Digital Service, PDS